2014
DOI: 10.1002/cam4.184
|View full text |Cite
|
Sign up to set email alerts
|

Access, excess, and overdiagnosis: the case for thyroid cancer

Abstract: The incidence of thyroid cancer in women is increasing at an epidemic rate. Numerous studies have proposed that the cause is increasing detection due to availability and use of medical diagnostic ultrasound. Our objective was to compare rates of diagnosis across different health-care regions to rates of diagnostic tests and to features of both health and access of the regional populations. This is a population-based retrospective ecological observational study of 12,959 patients with thyroid cancer between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
45
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 28 publications
(33 reference statements)
5
45
2
1
Order By: Relevance
“…However, between 1992 and 2012, incidence rates varied dramatically between provinces and even between regions within a province, as reported in Ontario. 15 In 2012, the highest incidence rates were in Ontario; BC had the lowest rates, at about half those in Ontario. The age-specific incidence curve had also dramatically changed, especially for women, and its shape differed among provinces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, between 1992 and 2012, incidence rates varied dramatically between provinces and even between regions within a province, as reported in Ontario. 15 In 2012, the highest incidence rates were in Ontario; BC had the lowest rates, at about half those in Ontario. The age-specific incidence curve had also dramatically changed, especially for women, and its shape differed among provinces.…”
Section: Discussionmentioning
confidence: 99%
“…25 This increasing use of imaging is mirrored by the increasing rates of thyroid cancer diagnosis, with the fourfold variation in diagnostic rates between regions correlating with patterns in the use of ultrasound, especially of the neck. 15 Kent and colleagues 22 found that the increase of thyroid cancer in Ontario is mainly due to small differentiated tumours, with the greatest increase in tumours less than 2 cm, considered nonpalpable and subclinical. These findings support the hypothesis that the increased incidence rates of thyroid cancer are due to overdiagnosis, with cases discovered incidentally in small tumours.…”
Section: Discussionmentioning
confidence: 99%
“…TC incidence is also increasing in Ontario, with significant regional variability (2). National Canadian data have suggested increased TC incidence in regions with the highest prevalence of foreign-born individuals (3).…”
mentioning
confidence: 99%
“…However, claiming that one or other trend totally accounts for the rise in the incidence of cancer would be to neglect the importance of the counterpart; so the most feasible explanation is that both trends are additive and complementary [51][52][53]. Other reasons may explain the marked increase in the frequency of papillary carcinoma, including:…”
Section: Discussionmentioning
confidence: 99%